A mouse model of gestation-specific transient hyperglycemia for translational studies. Issue 3 (March 2020) - Li, H Y; Liu, Y X; Harvey, L; Shafaeizadeh, S; van der Beek, E M; Han, W
Abstract : The prevalence of gestational diabetes mellitus (GDM) is estimated at 14% globally, and in some countries, such as Singapore, exceeds 20%. Both women and children exposed to GDM have an increased risk of later metabolic diseases, cardiovascular disease and other health issues. Beyond lifestyle changes and pharmaceutical intervention using existing type 2 diabetes medications for expecting women, there are limited treatment options for women with GDM; targeting better outcomes of potentially affected infants is unexplored. Numerous animal models have been generated for understanding of pathological processes of GDM development and for development of treatment strategies. These models, however, suffer from limited windows of opportunity to examine risk factors and potential intervention options. By combining short-term high-fat diet (HFD) feeding and low-dose streptozotocin (STZ) treatments before pregnancy, we have established a mouse model with marked transient gestation-specific hyperglycemia, which allows testing of nutritional and pharmacological interventions before, during and beyond pregnancy.